COMPUTERISATION OF LIBRARIES IN BANGLADESH - Zabed Ahmed, S.M.; Uddin Munshi, Md. Nasir; Uddin Ahmed, Minhaj (Malaysian Journal of Library and Information Science, 1997)
Examines the state of library computerisation in Bangladesh. Presents efforts made by different bodies and institutions in the country to automate their library operations and discloses problems faced by the libraries, which succeeded in automating some of their functions. Provides suggestions as to how libraries can adopt new computer technologies in order to improve their functions and services to users.